Impact of El Niño - Southern Oscillation (ENSO) and Indian Ocean Dipole (IOD) on Air Temperature in Bengkulu City - Edkayasa, Mardho Tillah; Yuliza, Elfi; Lizalidiawati, Lizalidiawati (JURNAL GEOCELEBES, 2025)
Bengkulu City has experienced rising air temperatures due to climate variability events, particularly ENSO and IOD. This study analyzes the relationship between ENSO, IOD, and air temperature in Bengkulu over the past 20 years (2004-2023) using data from Meteorological and Climatology stations, as well as ONI and DMI indices from NOAA. Pearson and multiple correlation analyses show a temperature increase of 0.08-0.1°C per year. ENSO has a stronger influence than IOD, especially on maximum temperature ( r = 0.28-0.38). To strengthen the analysis, multiple linear regression was applied, revealing that ONI had a statistically significant positive effect on average air temperature, while DMI showed a weaker and insignificant influence ( r = 0.10-0.11). A phase-based composite analysis revealed that average temperatures peaked during El Niño combined with Positive IOD phases, highlighting their synergistic warming effect, with maximum temperature reaching 35.9°C (February 2019), and the lowest minimum temperature recorded at 18°C (September 2019). The temperature increase during El Niño poses risks such as prolonged dry seasons, increased drought, and disruption of coastal ecosystems. Therefore, adaptation measures such as early warning systems and water resource management must be integrated into regional planning, particularly in agriculture and health sectors in Bengkulu.